THU0589 Patient-perceived coping was associated with patient-perceived quality of patient-physician interactions in 320 patients with rheumatoid arthritis. (15th June 2017) - Gossec, L; Desthieux, C; Cantagrel, A; Soubrier, M; Berthelot, JM; Joubert, JM; Combe, B; Czarlewski, W; Wendling, D; Dernis, E; Grange, L; Beauvais, C; et al.
Abstract : Background: There has been growing emphasis on the importance of shared decision-making in rheumatoid arthritis (RA). 1, 2 Patient-physician (pt-phy) shared decision-making necessitates open and thorough discussions and good interactions. Objectives: This analysis explored pt-perceived quality levels of pt-phy interactions and characteristics of pts when these interactions are described as very good by pts. Methods: CarNET (NCT02200068 ) was a French, 12-month, multicentre randomised controlled trial to assess access to an e-health platform (Sanoïa) allowing self-assessment of disease. 1, 2 This was a post-hoc analysis, using baseline data only. Pts had confirmed RA and were enrolled by their treating rheumatologist. Pt-perceived pt-phy interactions were assessed through the pt-reported questionnaire Perceived Efficacy in Patient-Physician Interactions (PEPPI-5) 3 which consists of 5 items, each starting with "How confident are you in your ability to ..." (eg. "... know what questions to ask a doctor?"). Pts rated each item on an 11-point scale; 0=not at all confident, 10=very confident. Total PEPPI-5 scores range from 0–50; higher scores represent higher perceived self-efficacy in pt-phy interactions. Factors associated with a higher PEPPI-5 (ie. >median) were analysed by univariate and multivariate logistic regression (factors included pt demographics, phy demographics, disease characteristics and activity including pt-perceived coping [scored 0–10 in the Rheumatoid Arthritis Impact of Disease (RAID) questionnaire; lower scores indicate better coping]). Results: Of 320 RA pts (159 vs 161; Sanoïa vs usual care), mean±SD age was 57.0±12.7 years, disease duration was 14.6±11.1 years and 253 (79.1%) were female. Mean DAS28 was 2.7±1.2, 54.1% were in DAS28 remission (<2.6); 216 (67.5%) were taking a biologic; 21.9% had previous therapeutic education sessions; 15.3% were members of pt associations; and 51.9% had followed university-level studies. The mean±SD PEPPI-5 score was 39.2±7.8 and the median was 40. In univariate analyses, associations with p<0.05 were observed between pt-perceived coping (p=0.0008), erosive disease (p=0.03) and DAS28 remission (p=0.05) and a high PEPPI-5; associations with p<0.2 were observed for older age (p=0.07) and HAQ-DI≤0.5 (p=0.12). In multivariate analyses, the only factor associated with high PEPPI-5 was pt-perceived coping (odds ratio [95% CI]=0.85 [0.76–0.96]; p=0.007). Conclusions: Among RA pts whose disease was well controlled, pt-perceived pt-phy interactions were good. Pt-perceived coping was associated with better pt-perceived pt-phy interactions, indicating that perhaps pts who felt in control were more at ease with their phy, or vice-versa. The data did not allow us to attribute causality. These elements are important in the shared decision-making process. References: www.sanoia.com. Gossec L. Arthritis Rheum 2016;68:S10. ten Klooster P. Patient Educ Couns 2012;87(1):125–30. Acknowledgements: This study was funded by UCB Pharma. We thank the patients and their caregivers in addition to the investigators and their teams who contributed to this study. Editorial services were provided by Costello Medical Consulting. Disclosure of Interest: L. Gossec Grant/research support from: UCB Pharma, Lilly, Consultant for: AbbVie, BMS, Celgene, Janssen, Novartis, MSD, UCB, C. Desthieux: None declared, A. Cantagrel: None declared, M. Soubrier: None declared, J. M. Berthelot: None declared, J. M. Joubert Employee of: UCB Pharma, B. Combe Grant/research support from: Merck Pfizer Inc, Roche-Chugai, Consultant for: Merck, Pfizer, Roche-Chugai, UCB Pharma, Bristol-Myers Squibb, Celgene, Eli Lilly, Speakers bureau: Merck, Pfizer, Roche-Chugai, UCB Pharma, Bristol-Myers Squibb, Celgene, Eli Lilly, Novartis, W. Czarlewski Employee of: UCB Pharma, D. Wendling: None declared, E. Dernis: None declared, L. Grange: None declared, C. Beauvais Speakers bureau: UCB Pharma, A. Perdriger: None declared, H. Nataf: None declared, M. Dougados Grant/research support from: UCB Pharma, AbbVie, Pfizer, Lilly, Merck, Novartis, H. Servy Shareholder of: Sanoïa platform operating company: e-health services, Employee of: Sanoia